EFEKTIVITAS MEKANISME PREVENTIF BERBASIS TEKNOLOGI IoT DAN SISTEM REPUTASI DALAM MENGURANGI SENGKETA SEWA MENYEWA MOBIL DALAM RANAH HUKUM PERIKATAN - Christian Immanuel Situmorang; Rafhael Roberto Silitonga; Callista Anastasia Shallom Poerba; Thalia Salma Putri Kamilah; Wardani Rizkianti (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
This article discusses the effectiveness of preventive mechanisms based on Internet of Things (IoT) technology and reputation assessment systems in reducing car rental disputes in the realm of binding law. The rapid growth of the car rental industry in Indonesia poses challenges in the form of potential defaults that are a major concern. Internet of Things (IoT) technology offers a solution by allowing vehicle owners to monitor the condition and location of the vehicle in real-time, this technology is also able to provide valid evidence if there is a breach of contract. The existence of a tenant rating system allows data-based assessment of the tenant's compliance history and contractual responsibilities so that this system can increase transparency and accountability, motivate tenants to act more responsibly, and make it easier for vehicle owners to assess the risk of prospective tenants. This research uses a normative juridical method with a literature study-based approach. This research found that the application of IoT technology can strengthen legal certainty and provide protection for rental owners against the risk of vehicle misuse. The combination of these two approaches is expected to build a safer, more effective, and sustainable car rental ecosystem. This research underscores the importance of detailed regulations and strict supervision to ensure the implementation of these technologies in the car rental industry.